Skin tissue engineering and regenerative medicine - Albanna, Mohammad Z.; Holmes, James H.; ScienceDirect eBooks (London : Academic Press, 2016)
The skin is the largest human organ system. Loss of skin integrity due to injury or illness results in a substantial physiologic imbalance and ultimately in severe disability or death. From burn victims to surgical scars and plastic surgery, the therapies resulting from skin tissue engineering and regenerative medicine are important to a broad spectrum of patients. Skin Tissue Engineering and Regenerative Medicine provides a translational link for biomedical researchers across fields to understand the inter-disciplinary approaches which expanded available therapies for patients and additional research collaboration. This work expands on the primary literature on the state of the art of cell therapies and biomaterials to review the most widely used surgical therapies for the specific clinical scenarios.
CONCLUSIONLIST OF ABBREVIATIONS; REFERENCES; 5 -- Process Development and Manufacturing of Human and Animal Acellular Dermal Matrices; INTRODUCTION; CLINICAL NEED; DEVELOPMENT OF ADMS; ADM REQUIREMENTS; PROCESSING METHODOLOGIES; Tissue Acquisition; Animal Dermis; Human Dermis; Decellularization Techniques; Physical Methods; Chemical Methods; Detergents; Acids or Bases; Hypotonic or Hypertonic Treatments; Alcohol and Other Solvents; Biologic Methods; Decellularization Criteria; Crosslinking; Preservation of ADMs; Wet Preservation; Cryopreservation; Freezing; Lyophilization; Sterilization.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed January 20, 2016).
Elsevier
Keywords: Tissue engineering; Skin -- Regeneration; Regenerative medicine; MEDICAL / Physiology; SCIENCE / Life Sciences / Human Anatomy & Physiology; Electronic books